Tree-ring chronologies, stable strontium isotopes and biochemical compounds: Towards reference datasets to provenance Iberian shipwreck timbers. (December 2020) - Domínguez-Delmás, Marta; Rich, Sara; Traoré, Mohamed; Hajj, Fadi; Poszwa, Anne; Akhmetzyanov, Linar; García-González, Ignacio; Groenendijk, Peter
Highlights: We compile and present novel datasets to determine provenance of shipwreck timbers. Tree-ring chronologies remain the most cost-effective datasets for wood provenancing. Seawater isotopic signal in shipwreck wood disguises original geochemical Sr ratios. Organic biomarkers discriminate living-trees species but fail with decayed wood. GIS can be used with probabilistic methods to pin-point origin of historic timber. Abstract: Studies on the provenance of wood for shipbuilding contribute widely to the fields of archaeology, anthropology, environmental history, cultural geography, and palaeoclimatology. The development of reference datasets to determine the date and provenance of shipwreck timbers is therefore a paramount undertaking. Here we compile and present recent advances in the development of tree-ring chronologies, stable strontium isotope ratios and chemical biomarkers aimed to determine the date and provenance of Iberian shipwreck timbers. A set of oak and pine tree-ring chronologies have been developed from living trees covering the past 500 and 800 years, respectively, and have served to confirm the provenance of the wood used in an 18th-century Spanish ship of the Royal Navy. Stable strontium isotopic signatures have been obtained from soil and living trees at 26 sites throughout the Iberian Peninsula, providing a climate-independent geochemical network to source the origin of historic timbers. However, retrieving the original isotopic signature from waterlogged samples remains unsuccessful, stressing the need to develop effective protocols to separate the seawater signal from the original strontium isotope ratios in the wood. Analyses of organic compounds in wood of living trees have proven suitable to discriminate species and provenances, but results on shipwreck timbers are inconclusive and should be further explored. Our regional approach has the potential to be expanded to other areas and archaeological timbers from different periods throughout the Anthropocene. We highlight the strengths and weaknesses of the techniques presented when applied to waterlogged wood, propose GIS tools to interpret and visualize combined results, and stress the need to expand these type of reference datasets to allow for multiproxy dendroprovenancing approaches.